Does Neurodiversity Have a Place in Adult Education’s Discussion of Diversity and Social Justice? - Tulare W Park; John Szabo; Kari Sheward; Carol Rogers-Shaw (Adult Education Research Conference, 2024)
This literature review explores the place of neurodivergent adults in Diversity, Equity, Inclusion, and Belonging policies and practices and the relationship between neurodiversity and social justice initiatives in adult education.
Keywords: neurodiversity; neurodivergent learners; adult education; social justice; DEIB